ORIENTASI PELAYANAN PUBLIK MELALUI PENDEKATAN NEW PUBLIC SERVICE UNTUK MENGATASI PROBLEM KESEHATAN PADA PROGRAM JAMKESMAS DI KECAMATAN KEMBARAN KABUPATEN BANYUMAS(PUBLIC SERVICE ORIENTATION THROUGH A NEW PUBLIC SERVICE APPROACH TO OVERCOME HEALTH PROBLEMS IN THE JAMKESMAS PROGRAM IN KEMBARAN SUB DISTRICT, BANYUMAS REGENCY) - Antono, Andi (Pembangunan Pedesaan, 2011)
The aim of this study was to describe health problems in implementing Jamkesmas (public health insurance) programme in Kembaran sub-distric of Banyumas Regency. To achieve this aim, this study explained how policy implementation based on the New Public Service overcoming the health problems of Jamkesmas. The study was conducted by using a qualitative method. Data was collected by in-depth interview with the beneficiaries of Jamkesmas offering village medical doctors of Puskesmas (public healts services) and officials of Kecamatan (sub-distric) in which that information was collected by using purposive sampling. The finding above showed that health problems were still difficult. The results indicated that the membership of health problems has not been completed; besides there were data inaccuracies, such as not following the procedures; bureaucratic; and social gaps. To overcome these problems, the orientation of policy action on the citizen; strategic thinking; and accountability services should be conducted.